2019
DOI: 10.3389/fpls.2019.00432
|View full text |Cite
|
Sign up to set email alerts
|

The DELLA Proteins Influence the Expression of Cytokinin Biosynthesis and Response Genes During Nodulation

Abstract: The key event that initiates nodule organogenesis is the perception of bacterial signal molecules, the Nod factors, triggering a complex of responses in epidermal and cortical cells of the root. The Nod factor signaling pathway interacts with plant hormones, including cytokinins and gibberellins. Activation of cytokinin signaling through the homeodomain-containing transcription factors KNOX is essential for nodule formation. The main regulators of gibberellin signaling, the DELLA proteins are also involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 64 publications
(117 reference statements)
0
10
0
1
Order By: Relevance
“…One of the most important gibberellin network regulators comprises DELLA proteins. In our previous study, we showed that PsDELLA1 and PsDELLA2 proteins had the most significant impact on pea–rhizobial symbiosis development [ 15 ]. Moreover, the expression levels of several BELL and KNOX genes were essentially decreased in the P. sativum mutants la cry-s ( della1 della2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important gibberellin network regulators comprises DELLA proteins. In our previous study, we showed that PsDELLA1 and PsDELLA2 proteins had the most significant impact on pea–rhizobial symbiosis development [ 15 ]. Moreover, the expression levels of several BELL and KNOX genes were essentially decreased in the P. sativum mutants la cry-s ( della1 della2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it has been shown that the exogenous treatment of S. tuberosum roots with gibberellins (GA3) is associated with decreased expression of several KNOX genes [ 9 ]. Moreover, it was recently shown that the expression levels of several KNOX and BELL genes are essentially decreased in P. sativum mutants, la cry-s ( della1 della2 ), with enhanced sensitivity to gibberellins due to impaired DELLA protein (negative regulators of plant response to these hormones) function [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In legumes, they also have a critical role for the establishment of the root nodule nitrogen-fixing symbiosis. Recently, DELLA proteins have been proposed to be also involved in the regulation of cytokinin genetic pathway through interaction with KNOX and BELL transcription factors (Dolgikh et al 2019). Thus, a focused analysis on the DELLA sequences from the Fabaceae family has been performed and showed similar evolutionary pattern compared to results discussed above.…”
mentioning
confidence: 84%
“…For example, during nitrogen-fixing symbiosis, DELLA is thought to be a key regulator of the infection process by directly regulating symbiotic genes NSP1/NSP2, ERN1, NF-YA1 and by enhancing the binding between CYCLOPS and NSP2 (Fonouni-Farde et al 2016;Jin et al 2016). Recently, DELLA proteins were also shown to be likely involved in the cytokinin genetic pathway regulation during nodulation in Pisum sativum L. (Dolgikh et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…DELLA gain of function mutant showed GA insensitivity and resulted into dwarf phenotype and vice-versa (Cheng et al, 2004;Wild et al, 2012). In addition to GA signalling, DELLAs were also involved in abscisic acid (ABA), auxin, brassinosteroids (BRs) and cytokinins (CKs) signalling, thereby regulating a range of growth and developmental processes in plants (Davière and Achard, 2016;Dolgikh et al, 2019). Genes including HAM, LAS, and MOC1 are reported to develop and maintain shoot apical and axillary meristem (Greb et al, 2003;Stuurman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%